Reactualizing Classical Islamic Power: Reinterpreting Al-Mawardi in Post-Reform Indonesian Democracy - Ahmad, Jafar (Jurnal Ushuluddin, 2025)
Imam Al-Mawardi, one of the most influential political thinkers in the history of Islamic civilization, provides a robust normative framework through the concept of al-imamah in his seminal work, Al-Ahkam al-Sulthaniyyah. Al-Mawardi emphasizes that power is not merely a tool for domination but a divine trust (amanah ilahiyah) that must be exercised to uphold justice, safeguard the public interest (maslahah), and protect the rights of the people. This study aims to analyze Al-Mawardi's concept of power and examine its relevance within the context of post-reform Indonesian democracy. The research employs a qualitative approach based on a literature review, utilizing a descriptive-comparative analysis technique to compare the normative framework of classical Islam with the principles of modern democracy. The findings indicate a convergence between the two systems regarding the legitimacy of power, public participation, and leadership accountability. Al-Mawardi, through the institution of ahl al-halli wa al-‘aqdi, provides a theoretical foundation for community representation in the leadership selection process, which functionally resembles elections in a democratic system. However, there are also epistemic tensions between the two, particularly concerning the source of sovereignty (God vs. the people) and the legal basis (Sharia vs. positive law). These findings reinforce the argument that classical Islamic political thought, when interpreted contextually rather than formalistically, can serve as a source of values to enhance the quality of substantive democracy in Indonesia